PENGEMBANGAN KURIKULUM IlMU PENGETAHUAN SOSIAL BAGI ANAK AUTIS KATEGORI RINGAN TINGKAT SEKOLAH DASAR - - Ruminiati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2013)
Abstract: Developing Social Studies Education Curriculum for Autistic Children with Mild Category in the Elementary School Level. The purpose of this research was to develop social studies education curriculum for autistic children with mild category in the elementary school level class I-III. This research and design used Borg & Gall design. Through some expert judgment, limited scale test, and extended scale test, this research produced the social studies education curriculum for autistic children with mild category in the elementary school level. The research results the social studies education curriculum for autistic children with mild category in the elementary school level comprised a competency standard in class I semester 1 understanding self identity and understanding colors. Semester 2: understanding self identity and understanding colors. Class II Semester I recognizing surrounding objects and recognizing a diversity of soy. Semester II love in family and recognizing types of job and tasks in ordinary life. Class III semester 1 with SK: understanding history of things, and Semester 2: understanding maintenances of animal, and semester 2: understanding maintenances of animals and understanding maintenances of surrounding objects.Abstrak: Penelitian ini bertujuan mengembangkan kurikulum matapelajaran Ilmu Pengetahuan Sosial (IPS) bagi anak autis kategori ringan untuk tingkat Sekolah Dasar (SD) kelas I-III. Penelitian pengembangan ini menggunakan rancangan/desain Borg & Gall. Setelah melalui serangkaian uji ahli, uji coba skala terbatas, serta uji coba skala luas dihasilkan produk berupa kurikulum IPS bagi anak autis tingkat SD kelas rendah kategori ringan. Hasil penelitian berupa Kurikulum IPS bagi anak autis kategori ringan kelas I-III SD meliputi Standar Kompetensi di kelas I semester 1 yaitu: memahami identitas diri, dan memahami berbagai warna. Semester 2 yaitu: memahami identitas diri, dan memahami berbagai warna. Kelas II semester 1: mengenal benda sekitar, dan mengenal macam-macam sayuran. Semester 2: kasih sayang di keluarga, dan mengenal berbagai pekerjaan dan tugasnya dalam kehidupan sehari-hari. Kelas III semester 1 dengan SK: memahami arah benda, dan semester 2: memahami pemeliharaan hewan, dan memahami pemeliharaan benda sekitar.Kata Kunci: kurikulum, IPS, autis, SD